An Exploratory Feasibility Study of Incorporating Volunteering Into Treatment for Adolescent Depression and Anxiety - Ballard, Parissa J.; Daniel, Stephanie S.; Anderson, Grace; Koehler, Aubry N.; Caballero Quinones, Elimarie; Strahley, Ashley; Nicolotti, Linda M. (Frontiers in Psychology, 2022)
Community volunteering is an under-utilized, at least under-researched, strategy to supplement existing treatment for affective disorders. We present findings from a feasibility study incorporating community volunteering into clinical treatment for depression and anxiety among adolescents and young adults. This exploratory pilot study had four aims: to investigate recruitment feasibility; to describe participants’ experiences with volunteering; to explore psychosocial assets by which volunteering might decrease depressive and anxiety symptoms; and to document preliminary changes in mental health outcomes before and after the volunteering intervention. Interviews and surveys were employed with participants (N = 9; ages 14-20, Mage = 16 years old,; 8 women and 1 man) newly diagnosed with: mild to moderate depression (single episode), mild to moderate anxiety, or adjustment disorder. Recruitment was feasible overall, successes and challenges are discussed. Experiences with volunteering were very positive. Qualitative findings revealed perceived positive effects of volunteering on mood and well-being such as helping with social anxiety and being a positive distraction. Qualitative findings revealed several psychosocial assets that improved related to volunteering (e.g., sense of purpose/meaning and sense of community). On average, participants reported a 19% decrease in depressive symptoms from the pre-survey (before volunteering) to the post-survey (after volunteering). Although more research is warranted, the implication of this study for practicing psychologists treating adolescents and young adults for mild to moderate depression and/or anxiety is that they may wish to consider incorporating community volunteer activities into treatment. Volunteering was a desirable activity for interested participants in treatment for affective disorders.